Motor subtype and cognitive decline in Parkinson's disease, Parkinson's disease with dementia, and dementia with Lewy bodies - Burn, D J (BMJ Group, 2006)
BACKGROUND: A previous cross sectional study found over‐representation of a postural instability gait difficulty (PIGD) motor subtype in Parkinson's disease patients with dementia (PDD) and dementia with Lewy bodies (DLB), compared with Parkinson's disease (PD). AIMS: (1) To examine rates of cognitive and motor decline over two years in PD (n = 40), PDD (n = 42) and DLB (n = 41) subjects, compared with age matched controls (n = 41), (2) to record whether motor phenotypes of PD, PDD, and DLB subjects changed during the study, (3) to find out if cognitive and motor decline in PD was associated with baseline motor subtype, and (4) to report the incidence of dementia in PD patients in relation to baseline motor subtype. RESULTS: Most of PDD and DLB participants were PIGD subtype at baseline assessment. In the non‐demented PD group, tremor dominant (TD) and PIGD subtypes were more evenly represented. Cognitive decline over two years was greater in PDD and DLB groups (mean decline in MMSE −4.5 and −3.9, respectively), compared with PD (−0.2) and controls (−0.3). There was an association between PIGD subtype and increased rate of cognitive decline within the PD group. Of 40 PD patients, 25% of the 16 PIGD subtype developed dementia over two years, compared with none of the 18 TD or six indeterminate phenotype cases (χ(2) = 6.7, Fisher's exact test p<0.05). CONCLUSION: A PIGD motor subtype is associated with a faster rate of cognitive decline in PD and may be considered a risk factor for incident dementia in PD.